Orexin Neurons Are Necessary for the Circadian Control of REM Sleep - Kantor, Sandor (Associated Professional Sleep Societies, LLC, 2009)
STUDY OBJECTIVES: The orexin-producing neurons are hypothesized to be essential for the circadian control of sleep/wake behavior, but it remains unknown whether these rhythms are mediated by the orexin peptides or by other signaling molecules released by these neurons such as glutamate or dynorphin. To determine the roles of these neurotransmitters, we examined the circadian rhythms of sleep/wake behavior in mice lacking the orexin neurons (ataxin-3 [Atx] mice) and mice lacking just the orexin neuropeptides (orexin knockout [KO] mice). DESIGN: We instrumented mice for recordings of sleep-wake behavior, locomotor activity (LMA), and body temperature (T(b)) and recorded behavior after 6 days in constant darkness. RESULTS: The amplitude of the rapid eye movement (REM) sleep rhythm was substantially reduced in Atx mice but preserved in orexin KO mice. This blunted rhythm in Atx mice was caused by an increase in the amount of REM sleep during the subjective night (active period) due to more transitions into REM sleep and longer REM sleep episodes. In contrast, the circadian variations of T(b), LMA, Wake, non-REM sleep, and cataplexy were normal, suggesting that the circadian timekeeping system and other output pathways are intact in both Atx and KO mice. CONCLUSIONS: These results indicate that the orexin neurons are necessary for the circadian suppression of REM sleep. Blunting of the REM sleep rhythm in Atx mice but not in orexin KO mice suggests that other signaling molecules such as dynorphin or glutamate may act in concert with orexins to suppress REM sleep during the active period. CITATION: Kantor S; Mochizuki T; Janisiewicz AM; Clark E; Nishino S; Scammell TE. Orexin neurons are necessary for the circadian control of REM sleep. SLEEP 2009;32(9):1127-1134.